Life Cycle Impact Assessment by Using LIME2 of Various Gold Leaching Systems from Metal Scrap Containing Gold - Seiji MATSUO; Sayuri TSUJI; Gjergj DODBIBA; Toyohisa FUJITA (Journal of MMIJ, 2016)
In recent years, global environmental problems, such as climate change and global warming, are receiving too much attention. Especially, the importance of biodiversity has been recognized since COP10, which was held in Japan in 2010. The aim of this study is to evaluate the gold extraction and recovery from waste materials in the context of Life Cycle Impact Assessment methodology, based on endpoint modeling. In this research, aqua regia, cyanide solution and ammonium thiosulfate solution were employed as leaching reagents. The gold exudation and recovery system were evaluated by LIME2, which is the Japanese version life cycle impact assessment method based on endpoint modeling. The system boundary includes pretreatment of the scrap, manufacturing process of leaching solution, Au recovery, processing of waste fluid and residual substances. Moreover, two scenarios for the pretreatment of a scrap were taken into consideration:(1) chelating resin was used in case of the low concentration, and (2) electrolytic winning was performed in case of the high concentration. Consequently, one of the main findings is that waste showed the largest load at influence domains in any case, and the rate of the load to social property was the largest at damage evaluation. Furthermore, the environmental load, in the case of using electrolytic winning was lower, when compared with the case where chelating resin adsorption was used. In other words, in order to lower the environmental burden, the grade of Au in the product exiting the pretreatment process should be increased.